Neighbourhood deprivation and small-for-gestational term births in the United States - Elo, Irma (2009)
Residential context has received increased attention as a possible contributing factor to race/ethnic and socioeconomic disparities in birth outcomes in the United States. Utilizing vital statistics birth record data, this study examined the association between neighbourhood deprivation and the risk of a term small-for-gestational-age (SGA) birth among non-Hispanic whites and non-Hispanic blacks in eight geographic areas: Baltimore City, Baltimore County, Montgomery County and Prince Georges County in Maryland, 16 pooled cities in Michigan, Durham County and Wake County in North Carolina, and Philadelphia, Pennsylvania. Multilevel random intercept logistic regression models were employed and statistical tests were performed to examine if the association between neighbourhood deprivation and SGA varied by race/ethnicity and study site. The risk of term SGA was higher among non-Hispanic blacks (range: 10.8%–17.5%) than non-Hispanic whites (range: 5.1%–9.2%) in all areas and it was higher in cities than in suburban locations. In all areas, non-Hispanic blacks lived in more deprived neighbourhoods than non-Hispanic whites. However, the adjusted associations between neighbourhood deprivation and term SGA did not vary significantly by race/ethnicity or study site. The summary fully-adjusted pooled odds ratios, indicating the effect of one standard deviation increase in the deprivation score, were 1.15 [95% CI: 1.08–1.22] for non-Hispanic whites and 1.09 [95% CI: 1.05–1.14] for non-Hispanic blacks. Thus, neighbourhood deprivation was weakly associated with term SGA among both non-Hispanic whites and non-Hispanic blacks.